INOVASI PEMBELAJARAN AKTIF MELALUI PENGGUNAAN STRATEGI READING GUIDEDAN MIND MAPPING PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM DI MADRASAH ALIYAH - Ahmad Fauzi (Didaktika : Jurnal Kependidikan, 2019)
Islamic cultural history lesson generally contain historical aspects of Islam. The learning cultural history (SKI), however, often looks boring for manys students. To overcome this problem, it is necessary to implement active learning innovations with multiple strategies. This study aims to describe the implementation of the strategy reading guideand mind mapping in SKI learning at MAS Tarbiyatus Shibbyan.This is a quantitative field research involving 12 students. Data was collected through observation, interview, and literature review, which were then analyzed descriptively. The results show that the reading guideand mind mapping strategies had been well applied to the SKI subjects in Class XI so that they were able to foster student learning activities. However, in its implementation, it is necessary to develop learning by continuing to use these two strategies simultaneously by paying attention to aspects such as the material presented and the conditions of students in the class. In addition, innovation can also be carried out using reflective strategies that will help students reflect on attitudes that should be emulated or avoided in the series of historical events that are being studied.Keywords: active learning, map mapping, reading guide